2016
DOI: 10.1590/1806-9282.62.04.353
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and abdominal obesity in adults living with HIV/AIDS

Abstract: Objective: To investigate the prevalence of overweight, abdominal obesity and associated factors in people living with HIV/AIDS (PLWHA). Method: Cross-sectional study with 270 PLWHA. A questionnaire was applied to investigate sociodemographic, clinical and lifestyle characteristics. Weight, height and waist circumference were measured. BMI ≥25 kg/m 2 was considered overweight, while abdominal obesity referred to waist circumference ≥102 cm for men and ≥88 cm for women. The authors used multiple Poisson regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
14
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 25 publications
(50 reference statements)
7
14
1
Order By: Relevance
“…Relative to patients aged greater than 50, patients aged between 18-30, are 60% times less likely to develop the risk of being overweight (AOR=0.4,95% CI (0.2,0.9). This is in line with the finding that observed in Tanzania and brazil that showed overweight and obesity were more prevalent in older patients, with the oldest age-group (>50 years) having the highest burden (18,19). This might be due to the relative risk curves of overweight and obesity reach maximum point in the mid-50s and then declines.…”
Section: Discussionsupporting
confidence: 91%
“…Relative to patients aged greater than 50, patients aged between 18-30, are 60% times less likely to develop the risk of being overweight (AOR=0.4,95% CI (0.2,0.9). This is in line with the finding that observed in Tanzania and brazil that showed overweight and obesity were more prevalent in older patients, with the oldest age-group (>50 years) having the highest burden (18,19). This might be due to the relative risk curves of overweight and obesity reach maximum point in the mid-50s and then declines.…”
Section: Discussionsupporting
confidence: 91%
“…A predominance of HIV cases was found in men (51.4%), a result corroborated with data from the Ministry of Health 17 and other national surveys 18,19 .…”
Section: Discussionsupporting
confidence: 87%
“…As in other studies 18,20,25 it was observed that most of the men (61.1%) were classified with adequate nutritional status, while most women (47.1%) were overweight or obese. In the present study, women had a significantly lower education level compared to men, indicating an inverse relationship between schooling and overweight.…”
Section: Discussionsupporting
confidence: 79%
“…This is in line with the finding that observed in Tanzania and brazil that showed overweight and obesity were more prevalent in older patients, with the oldest age-group (>50 years) having the highest burden. 17,18 This might be due to the relative risk curves of overweight and obesity reach maximum point in the mid-50s and then declines.…”
Section: Discussionmentioning
confidence: 99%